Enhanced removal efficiency of sulfamethoxazole by acclimated microalgae: Tolerant mechanism, and transformation products and pathways. (March 2022) - Zhang, Yibo; Wan, Jing; Li, Zhang; Wu, Zhenbing; Dang, Chenyuan; Fu, Jie
Graphical abstract: Highlights: Acclimation enhanced resistance of Chlorella vulgaris to sulfamethoxazole toxicity. Increase of catalase and glutathione reductase was critical tolerant mechanism. Acclimated C. vulgaris exhibited enhanced removal of sulfamethoxazole. Biodegradation was the major removal mechanism of sulfamethoxazole by C. vulgaris . Abstract: This study utilized sulfamethoxazole (SMX) acclimatization to enhance the tolerance and biodegradation capacity of Chlorella vulgaris . Compared to wild C. vulgaris, the growth inhibition and oxidative damage induced by SMX evidently decreased in acclimated C. vulgaris, and meanwhile photosynthetic and antioxidant activities were significantly promoted. The physiological analyses with the aid of principal component analysis revealed the increase of catalase and glutathione reductase activities was the critical tolerant mechanism of acclimated C. vulgaris . As the consequence, the acclimated C. vulgaris exhibited enhanced efficiency and (pseudo-first-order) kinetic rate for removal of SMX. The distribution analysis of residual SMX demonstrated the biodegradation was the major removal mechanism of SMX by C. vulgaris, while bioadsorption and bioaccumulation made pimping contributions. During the degradation process of SMX, nine transformation products (TPs) were identified. Based on the identified TPs, a possible transformation pathway was proposed.